Toward a historiography of the lesbian transsexual, or the TERF's nightmare. Issue 2 (29th March 2022) - Gill-Peterson, Jules
Abstract: This essay asks after the possibility of making the transsexual lesbian signify as a historical mode of sexuality, as a contribution to an anti-TERF method in trans and lesbian studies. What logics of mid twentieth century gender and sexuality are responsible for the opacity of transsexual and transvestite lesbians prior to the 1970s, despite the ample evidence that desire between femmes played a central role in trans social life? To move towards such a historiography and method, the author considers two paradigmatically difficult cases. First, Louise Lawrence, a well-known trans women in the San Francisco Bay Area who transitioned entirely do-it-yourself in 1944, and whose long term relationship with a partner, Gay Elkins, is high opaque in the archival record. Second, the essay considers the compulsory heterosexuality embedded in the medical logic of transsexuality in the 1960s, arguing that the medical ontology of the transsexual vagina was itself dependent upon the avowal of its immediate and exclusive use for penetration by straight men, making transsexual lesbians implausible despite their evident existence.